2004
DOI: 10.1242/jcs.01492
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of keratinocyte chemokinesis and chemotaxis through distinct nicotinic receptor subtypes

Abstract: Nicotinergic agents can act as both chemokines and chemoattractants for cell migration. Epidermal keratinocytes both synthesize acetylcholine and use it as a paracrine and autocrine regulator of cell motility. To gain a mechanistic insight into nicotinergic control of keratinocyte motility, we determined types of nicotinic acetylcholine receptors and signaling pathways regulating keratinocyte chemokinesis and chemotaxis, using respective modifications of the agarose gel keratinocyte outgrowth assay. Random mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
80
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 117 publications
5
80
0
1
Order By: Relevance
“…Further, UVR exposure is a common and wellcharacterized method of inducing inflammation in the skin, and we have employed this method for many years to study this effect Gahring et al, 1984). Keratinocyte expression of nAChR has been demonstrated to have important roles in keratinocyte adhesion and motility (Chernyavsky et al, 2004;Grando et al, 1995;Zia et al, 1997), differentiation (Arredondo et al, 2002;Grando et al, 1996), apoptosis (Arredondo et al, 2003;Nguyen et al, 2001), and certain components of inflammation (Kalayciyan et al, 2007;Kurzen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Further, UVR exposure is a common and wellcharacterized method of inducing inflammation in the skin, and we have employed this method for many years to study this effect Gahring et al, 1984). Keratinocyte expression of nAChR has been demonstrated to have important roles in keratinocyte adhesion and motility (Chernyavsky et al, 2004;Grando et al, 1995;Zia et al, 1997), differentiation (Arredondo et al, 2002;Grando et al, 1996), apoptosis (Arredondo et al, 2003;Nguyen et al, 2001), and certain components of inflammation (Kalayciyan et al, 2007;Kurzen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…102 Activation of the a3 nAChR induces KC migration via PKCd and RhoA, activation of a7 nAChR induces KC migration via PI3K and Rac/Cdc42, and activation of a9 nAChR induces KC migration both in vitro and in vivo by modulating cell-cell and cell-ECM adhesion. 103,104 The a7 nAChR and M1 mAChR enable KCs to sense ACh gradients, which initiates polarization of the cell and expression of a 2 and a 3 integrins at the leading edge of the cell via activation of the Ras/Raf-1/MEK1/ERK pathway, resulting in the stabilization of lamellipodia at the leading edge during the initial steps of AChmediated chemotaxis. 103 Lastly, activation of the mAChR M4 induces KC migration both in vitro and in vivo by upregulating the ''migratory'' integrins a 5 b 1 , a v b 5 , and a v b 6 , and activation of the mAChR M3 inhibits KC migration both in vitro and in vivo by upregulating the ''sedentary'' integrins a 2 b 1 and a 3 b 1 .…”
mentioning
confidence: 99%
“…ACh and its congeners are chemotactic for KCs, neurons, and other cell types (2)(3)(4)(5)(6)(7)(8). To characterize the physiologic control of keratinocyte migration, we developed an in vitro model of skin epithelialization, termed the agarose gel keratinocyte outgrowth system (AGKOS) (9).…”
mentioning
confidence: 99%
“…To characterize the physiologic control of keratinocyte migration, we developed an in vitro model of skin epithelialization, termed the agarose gel keratinocyte outgrowth system (AGKOS) (9). Using AGKOS, we have demonstrated that activation of the keratinocyte nicotinic ACh receptors (nAChRs) comprised by ␣7 subunits exhibit reciprocal effects on cell motility by stimulating directional (chemotaxis) and inhibiting random (chemokinesis) migration and that ACh-gated ion channels containing ␣3 subunit stimulate chemokinesis of KCs (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation